(untitled) (Revista Puertorriqueña de Psicologia, 2022)
This is the second number of the volume 32 of 2021 of the Puerto Rican Journal of Psychology. The 2021 has been a year of many challenges. Still immersed in the middle of a pandemic for about two years, despite scientific advances, particularly with the development of effective vaccines, was unthinkable for many. This reality reminds us that scientific advances do not automatically translate into real changes in the quality of life of communities. The dire history of unethical clinical trials with African American and Latino communities could be one of the many factors that are contributing to people’s mistrust of COVID-19 vaccines. However, history also reminds us that science alone is not enough to produce changes in prevention and intervention practices in communities. Educative effort with transparency and with the involvement of communities is required to be more effective in translating science into concrete actions. The imposition approach used by government agencies has been shown to create more resistance and does not address the real concerns that people may have around vaccines and the measures that have been imposed to mitigate the pandemic. A comprehensive approach is required to address the fears, concerns, and misinformation that have permeated during the pandemic. The implementation of science in disconnection from communities does not allow progresses in the translation of it into changes in behaviors, beliefs and practices that advance us towards the resolution of a pandemic state. Punitive efforts, beyond joining forces, tarnish people’s ability to do what is right for their well-being and the people who make up their community. Why we are not appealing to the values and virtues of human nature to follow security protocols? Why focus on a state of repression and not educate on what we can do and how we can use safety measures to reduce infections? History tells us that pandemics can take several years and for our immune defenses to learn to co-exist with the virus. It will be important to use strategies that connect and highlight those values that promote personal and collective well-being. Science disconnected from communities and their practices, faces the possibility of being a science only for those who practice science and not for the general population.